Fisheries Management and Climate Change in the Northeast Atlantic Ocean and the Baltic Sea (Copenhagen : Nordic Council of Ministers, 2008)
A conference on "Fisheries Management and Climate Change in the Northeast Atlantic Ocean and the Baltic Sea" was convened in Bergen, Norway, 17-18 April 2008. The themes covered included climate change-related physical and biological changes in the oceans and the implications for fisheries and aquaculture activities and their sustainable management. It was concluded that there is a need to design monitoring strategies to detect critical changes in species and ecosystems, implement responsive management that can adjust quickly, identify species and ecosystems that are sensitive to changes in climate, anticipate changes in distribution and prepare responses that avoid management conflicts, maintain (or rebuild) resilience of marine ecosystems and fish stocks, and understand the socio-economic consequences of climate change on fisheries. The research that is required to underpin the preceding must be interdisciplinary and ecosystem based. However, the fisheries and marine science sectors in the Nordic countries are currently underfinanced and, therefore, are unable to expand their activities to accomplish this.